Case Report: Identification of a novel hemizygous missense RPL10 gene variant in two unrelated patients - Xu, Lixia; Wu, Ke; Cong, Yan (Frontiers in Pediatrics, 2025)
The X-linked syndromic intellectual developmental disorder-35 (MRXS35; OMIM#300998) is caused by variants in the RPL10 gene (OMIM*312173) on chromosome Xq28. Patients with MRXS35 mainly present with intellectual disability (ID), psychomotor development delay, speech delay, short stature, craniofacial anomalies, hypotonia, seizures, gastrointestinal problems, genitourinary anomalies, cardiac anomalies, eye defects, and hearing loss. Herein, we are the first to report two unrelated Chinese patients with the same novel hemizygous missense RPL10 gene variant. Two male patients from two different families were admitted to the hospital for genetic counseling. In the first months of life, both newborns presented with congenital laryngeal stridor, feeding difficulties, neonatal pneumonia, neonatal hypoglycemia, dysmorphic features, and bilateral cryptorchidism. At his last clinical evaluation at 9 years of age, case II presented with ID, speech delay, short stature, and craniofacial anomalies. Whole-exome sequencing identified the same hemizygous missense RPL10 gene variant (NM_006013.5:c.347G>A, p.Arg116Gln) in each patient, inherited from their respective mothers. The functional analysis of this variant in vitro demonstrated that this missense RPL10 gene variant (c.347G>A) reduced the mRNA expression of the RPL10 gene, thereby decreasing synthesis of the RPL10 protein. Our in vitro functional analysis indicated a loss-of-function effect of RPL10 gene variants.